Detection of formaldehyde in cheese using FTIR spectroscopy - Alkhalf, Maha Ibrahim; Mirghani, Mohamed Elwathig Saeed (Faculty of Food Science & Technology, Universiti Putra Malaysia (UPM)""", 2017)
A new analytical method was developed for determining formaldehyde (CH2O) in cheese by FTIR spectroscopy. Formaldehyde (CH2O) was also spiked at 0 to 100 mg/100g in freshly prepared cheese. Two sets, each of twenty one (21) samples, were prepared using the same type of soft white cheese. FTIR spectra were recorded using Attenuated Total Reflectance accessory at room temperature, and the Partial Least Squares (PLS) regression statistical method was used to derive calibration models for the set of samples in triplicates. The spectral region used for correlation and cross validation were set include the data from 1650 – 800 cm–1. As suggested by the correlation and variance spectra. The coefficient of determination (R2) of correlation was found to be 0.986 with average standard error of calibration (SEC) of 2.24 mg/100g, with. The calibration model was validated by using the “leave-one-out” cross-validation method, and the R2 of validation, the standard errors of prediction (Yang & Irudayaraj), and standard deviation (Angulo et al.) of the differences for repeatability and accuracy were computed and found to be 0.9662, 4.07mg/100g and 4.61, respectively. The results support the premise that FTIR spectroscopy is an efficient, precise and rapid analytical technique for the determination of minor components such as formaldehyde / formalin in cheese samples.